Platelets in Hematologic and Cardiovascular Disorders (A Clinical Handbook) - Gresele, Paolo (Cambridge University Press, 2013)
Progress in the field of platelet research has accelerated greatly over the last few years. If we just consider the time elapsed since our previous book on platelets (Platelets in Thrombotic And Non-Thrombotic Disorders, 2002), over 10 000 publications can be found in a PubMed search using the keyword “platelets.” Many factors account for this rapidly expanding interest in platelets,amongthemanexplosive increase in the knowledge of the basic biology of platelets and of their participation in numerous clinical disorders as well as the increasing success of established platelet-modifying therapies in several clinical settings. All of this has led to the publication of several books devoted to platelets in recent years. Nevertheless, it is surprising that none of these is a handbook that presents a comprehensive and pragmatic approach to the clinical aspects of platelet involvement in hematologic, cardiovascular, and inflammatory disorders and the many new developments and controversial aspects of platelet pharmacology and therapeutics.